Penerapan Metode Bernyanyi Untuk Meningkatkan Hasil Belajar Bahasa Arab - Siska; M Wisnu Khumaidi; Rima Ajeng Rahmawati (Al Mitsali, 2023)
This research is based on the low results of learning Arabic owned by grade IV SDIT Baitul Jannah Bandar Lampung so that it can improve Arabic learning outcomes. generate a sense of joy and joy in students, and can solidify knowledge in the minds of students. The formulation of the problem in this study is. "Can the application of the singing method improve student learning outcomes in the fourth grade Arabic language subjects at SDIT Baitul jannah Bandar Lampung". The research objective is to find out whether the singing method can improve student learning outcomes in learning Arabic for grade IV SDIT Baitul Jannah Bandar Lampung for the 2019/2020 academic year. The research was carried out in 2 cycles with each cycle containing three learning meetings. Based on the formulation of the problem and research objectives, the implementation of this research is to use a type of qualitative research, namely Classroom Action Research (PTK). PTK is an approach in class-based research to help improve teacher teaching methods in order to improve student learning outcomes in class. The results showed that the application of the singing method can improve the learning outcomes of Arabic students in grade IV even semester at SDIT Baitul jannah Bandar Lampung in the 2019/2020 school year, This is indicated by an increase in the written and singing test results in each cycle. In the first cycle to the second cycle, the average score of the written test was 88.91 to 96.78 and the singing test with an average value of 82.95 to 89.22.